Investigation of refractive index dispersion and electrical properties in carbon nano-balls' doped nematic Liquid crystals - Okutan, M; San, SE; Köysal, O; Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2005)
Electrical and refractive index dispersion properties of a carbon nano-balls' (Fullerene C-60) doped Liquid crystal (LC) composite, are investigated by concerning the frequency-dependent dielectrical properties, laser-induced effects on current-voltage (I-V) characteristics and optical characteristics suggest that the samples exhibit voltage-controlled differential negative resistance behavior. Dielectric spectra reflect the presence of different relaxation modes at higher frequencies. The refractive index dispersion parameters (oscillator energy and strength, optical moments) were also determined by optical characterization. As a result, C60 doping changes photoconductivity, dielectric and refractive index properties of LC in a favorable manner. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Liquid crystal; Fullerene (C-60); current-voltage; impedance spectroscopy